Copper detoxification machinery of the brain-eating amoeba Naegleria fowleri involves copper-translocating ATPase and the antioxidant system - Maria Grechnikova; Kateřina Ženíšková; Ronald Malych; Jan Mach; Robert Sutak (International Journal for Parasitology: Drugs and Drug Resistance, 2020)
Copper is a trace metal that is necessary for all organisms but toxic when present in excess. Different mechanisms to avoid copper toxicity have been reported to date in pathogenic organisms such as Cryptococcus neoformans and Candida albicans. However, little if anything is known about pathogenic protozoans despite their importance in human and veterinary medicine. Naegleria fowleri is a free-living amoeba that occurs naturally in warm fresh water and can cause a rapid and deadly brain infection called primary amoebic meningoencephalitis (PAM). Here, we describe the mechanisms employed by N. fowleri to tolerate high copper concentrations, which include various strategies such as copper efflux mediated by a copper-translocating ATPase and upregulation of the expression of antioxidant enzymes and obscure hemerythrin-like and protoglobin-like proteins. The combination of different mechanisms efficiently protects the cell and ensures its high copper tolerance, which can be advantageous both in the natural environment and in the host. Nevertheless, we demonstrate that copper ionophores are potent antiamoebic agents; thus, copper metabolism may be considered a therapeutic target.